Karakteristik Musikal Lagu Yesus Bertanya Karya RP Redemptus Simamora - Jones Irawan Sibagariang; Junita Batubara; Emmi Simangunsong (Institut Seni Indonesia Denpasar, 2022)
Purpose: This study aims to discuss the musical characteristics of the song Yesus Bertanya by RP Redemptus Simamora. In this study, the author uses the theory of P. Malm and Prier as the author's foundation in knowing the characteristics of the song Yesus Bertanya. The song Yesus Bertanya has a simple musical characteristic and has deep meaning in the lyrics. Research method: In this study the authors used a qualitative descriptive research method. Result and discussion: The form of the song Yesus Bertanya is Ternary Form or a three-part song form consisting of A(a'), B(b'), C(c',c'). And the song Yesus Bertanya consists of part A (Vers), part B (Pre Chorus), part C (Ref). Implication: The meaning contained in the song Yesus Bertanya is to describe the doubts and anxiety of mankind from all ages who still question who Jesus is, so that we are invited to contemplate who Jesus is. Jesus is everything to us in joy and sorrow and Jesus is the love of all human hearts